0484 Trouble Sleeping Predicts Future Decreased Quality of Life in Young Children with Fontan Circulation. (25th May 2022) - Combs, Daniel; Partha, Meghana; Hsu, Chiu-Hsieh; Edgin, Jamie; Seckeler, Michael; Klewer, Scott; Parthasarathy, Sairam; Cooper, David
Abstract: Introduction: Children with congenital heart disease who undergo a Fontan procedure are at higher risk of reduced health-related quality of life (HR-QOL) compared to age-matched peers. We have previously shown that current sleep disturbances are associated with decreased HR-QOL, but there is no existing longitudinal data on the relationship between sleep disturbance and HR-QOL in children with Fontan circulation. Methods: We analyzed data from the Pediatric Heart Network Single Ventricle Reconstruction follow up study to evaluate associations between parent-reported trouble sleeping with HR-QOL as measured by the child health questionnaire (CHQ, measured at age 6 years) as well as the Pediatric Quality of Life questionnaire (PedsQL, measured at baseline as well as age 4, 5 and 6 years) in children with Fontan circulation. Presence of trouble sleeping was assessed at baseline and quality of life was assessed at baseline (age 3 years old) and annually for 3 years. Analysis was performed using the Wilcoxon sum rank test. Results: 227 participants had data at baseline (age 3 years), and 196 participants completed HR-QOL measures at all time points. Parent-reported trouble sleeping was reported "often" or "almost always" in 11% of participants. Baseline trouble sleeping predicted decreased HR-QOL at all future time points, particularly psychosocial HR-QOL. Psychosocial HR-QOL as measured by the Peds QL was significantly lower at all time points in the group with trouble sleeping. At age 6 years, psychosocial HR-QOL remained significantly lower in the group with trouble sleeping at baseline on both the PedsQL (median score 78 [interquartile range 63, 90] vs 65 [58, 83], p=0.03) and the CHQ (median t-score 54 [47, 59] vs 47 [42, 53], p=0.002). Conclusion: Trouble sleeping in children with Fontan circulation predicts future decreased HR-QOL. Better understanding of sleep problems is needed in children with Fontan circulation as sleep disorder treatment may lead to improved HR-QOL in this at-risk population. Support (If Any): Funding to DC from the American Heart Association and NIH-NHLBI. Single Ventricle Reconstruction study data obtained from the Pediatric Heart Network.